2022
DOI: 10.1136/openhrt-2021-001936
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dapagliflozin treatment on renal function and diuretics use in acute heart failure: a pilot study

Abstract: ObjectiveTo determine the impact of sodium-dependent glucose type 2 cotransporter inhibitors on the renal function in acute heart failure.MethodsIn a single-centre, controlled, randomised study, patients were prescribed dapagliflozin in addition to standard therapy, or were in receipt of standard therapy. The prespecified outcome was renal function deterioration; the secondary outcomes were the development of resistance to diuretics, weight loss, death during hospitalisation and the rehospitalisation or death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 55 publications
0
15
0
3
Order By: Relevance
“…Due to high heterogeneity, we performed a leave-one-out sensitivity analysis by iteratively removing one study at a time to ensure the results were not dependent on a single study. The removal of each study from the pooled analysis did not affect the WRF endpoint, except for the study from Charaya et al [ 22 ]. The withdrawal of this study reduced the frequency of WRF in the SGLT2i group compared with the control group and eliminated the heterogeneity in the endpoint (OR 0.64; 95% CI 0.43–0.95; p = 0.029; I 2 = 0%; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to high heterogeneity, we performed a leave-one-out sensitivity analysis by iteratively removing one study at a time to ensure the results were not dependent on a single study. The removal of each study from the pooled analysis did not affect the WRF endpoint, except for the study from Charaya et al [ 22 ]. The withdrawal of this study reduced the frequency of WRF in the SGLT2i group compared with the control group and eliminated the heterogeneity in the endpoint (OR 0.64; 95% CI 0.43–0.95; p = 0.029; I 2 = 0%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fifth, the outcomes of mean daily urinary output and mean daily dose of loop diuretics were based on small samples, as these outcomes were not reported in all studies, with broad confidence intervals and high heterogeneity. And, finally, the endpoint of WRF had elevated heterogeneity, identified as originating from Charaya et al [ 22 ]. This study found a non-statistically significant increase in WRF with SGLT2i relative to no SGLT2i therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Transient GFR reduction is considered a sign of successful decongestion and it is not associated with loss of functional nephrons. [22] A retrospective study from the EMPA REG OUTCOMES trial database divided the patients into three groups depending on the GFR decrease during therapy with empagliflozin: >10%, 0-10%, and no change. For those patients exposed to empagliflozin 10 -25 mg, there were 41% non-dippers, 31% with intermediary response, and 28% dippers.…”
Section: Sglt 2 Inhibitor Trialsmentioning
confidence: 99%
“…Our search retrieved six RCTs [59][60][61][62][63][64] and two observational studies [65,66], in total. Of note, one trial, the Effect of Sotagliflozin on Cardiovascular Events in Patients with Type 2 Diabetes Post-Worsening Heart Failure (SOLOIST-WHF) trial [64] enrolled subjects with T2DM and a recent hospitalization for acute decompensation of HF, therefore, it did not assess the safety and efficacy of SGLT-2 inhibitors in the "strict" setting of acute HF.…”
Section: Resultsmentioning
confidence: 99%